2009
DOI: 10.1080/13668250902845236
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment, stress, and growth from parenting an individual with an autism spectrum disorder

Abstract: These findings suggest that although stress is a major concern for caregivers, enrichment and growth may also occur in varying degrees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
80
2
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(96 citation statements)
references
References 26 publications
10
80
2
4
Order By: Relevance
“…Similar to the extant literature (Gray, 1994(Gray, , 1997Hutton & Caron, 2005, Montes & Halterman, 2007Phelps, et al, 2009), the parents of young children with ASD in our study reported impaired family functioning in several ways. For example, mothers spoke of how difficult it is to do normal or spontaneous family activities, because family life with a child with ASD has to be very structured and planned.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Similar to the extant literature (Gray, 1994(Gray, , 1997Hutton & Caron, 2005, Montes & Halterman, 2007Phelps, et al, 2009), the parents of young children with ASD in our study reported impaired family functioning in several ways. For example, mothers spoke of how difficult it is to do normal or spontaneous family activities, because family life with a child with ASD has to be very structured and planned.…”
Section: Discussionsupporting
confidence: 78%
“…Sometimes mothers also reported marital strain because of conflicts about their child's upbringing. In line with the evidence of parents' strengths and resilience in coping with the diagnosis of ASD, as found in past studies (Bayat, 2007;Davis & Carter, 2008;Phelps et al, 2009), the mothers in our study also have shown to do 'all they can' for their child with ASD. However, in spite of this, many of mothers' questions and concerns remained unanswered.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…For example, 'stress' is often examined in a fragmented manner as studies rarely synthesise the broad range of contributing factors, such as dispersion of responsibilities, boundaries between family members and personal meanings of having a family member with ASD (Lecavalier et al, 2006;Miodrag and Hodapp, 2010). Another important limitation is that there is reliance on maternal perspectives as representative of the whole family (Phelps et al, 2009b;Smith et al, 2010). Maternal perspectives are important but may not necessarily reflect those of other family members (Seligman and Darling, 2007).…”
Section: Family-focused Asd Research To Date and Its Limitationsmentioning
confidence: 99%
“…Due to these and other issues, many families living with ASD experience more stress than families with both neurotypically developing children and children with other disabilities (Altiere and Von Kluge, 2009;Hastings, 2003b;Johnson et al, 2011;Miodrag and Hodapp, 2010;Rao and Beidel, 2009). Additionally, some families living with ASD report negative outcomes on family functioning, evidenced by higher levels of psychological problems, greater emotion rather than problem-focused coping strategies and higher family conflict (Meadon and Stoner, 2010;Phelps et al, 2009b).…”
Section: Family-focused Asd Research To Date and Its Limitationsmentioning
confidence: 99%